Pengaruh Penggunaan Media Animasi Berbantuan Edmodo Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Ekonomi Kelas XI A MA Nurul Hilal Senuro - Musdalipah Musdalipah; Ikbal Barlian; Edutivia Mardetini (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
The research aimed to prove the effect used of edmodo-assisted animation media on the students learning results in economic subject at the students class A in eleventh grade of the Nurul Hilal Senuro Islamic High School. This was experimental study that used pre-experimental design in one group pretest-posttest design. The population of this study were all of the eleventh grade students of the Nurul Hilal Senuro Islamic High School. The sampling technique used cluster random sampling by drawing so it’s obtained students class A in eleventhgrade as experimental grade. Collected data used by test and observation. The data analysis techniques from students learning results data were obtained through the pre-test and post-test results, while the data observation analyses were taken by observer’s observation during the learning process. Acquisition of the t-test used test sample related that is tcounted = 51,15 and ttable = 2,0063. Get it 2,0063 < 51,15 > 2,0063, so null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. Thus, it could be concluded that there was the effect used of edmodo-assisted animation media on the students learning results in economic subject at the students class A in eleventh grade of the Nurul Hilal Senuro Islamic High School. It is recommended when learning using edmodo-assisted animation media teachers should pay attention to the creation of animation media well, the creation of edmodo accounts of learners and the guidance of their use, as well as conditioning of learners during learning.DOI: https://dx.doi.org/10.17977/UM014v15i12022p037